Trauma-Informed school practices: Creating positive classroom culture. Issue 4 (8th August 2022) - Morton, Brenda M.
Abstract: The middle school years can be exciting and confusing for young adolescent students. Thus it is important for teachers, administrators, and school professionals to create a unique classroom and school culture that meets their needs. Creating a positive classroom culture that supports young adolescents through social, physical, and academic development can be complex. For instance, significant numbers of young adolescents have or are experiencing traumatic events that can exacerbate their academic performance. Implementing mental health strategies based on trauma-response practices in the middle school classroom can promote healthy mind-sets, help students regain safety and stability, and put them back on track for academic and social success. This article presents specific factors that make middle school students unique and advocates for educators to implement trauma-response best practice strategies into their daily classroom practice. Including these strategies can support young adolescent development, including the mental well-being of students, and promote a positive and productive classroom environment.